PENGARUH NPF, BOPO DAN FDR TERHADAP RETURN ON ASSETS (ROA) PADA BANK UMUM SYARIAH - Dinda Naza Febriani; Gusganda Suria Manda (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to test the influence of Non-Performing Financing (NPF), Operating Costs on Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on Return on Assets (ROA). The results of this study showed that Non-Performing Financing (NPF) and Operating Costs to Operating Income (BOPO) had a significant negative effect on Return on Assets (ROA) while Financing to Deposit Ratio (FDR) had a significant positive effect on Return on Assets (ROA). The predicting ability of the three variables against Return on Assets (ROA) in this study was 96.70%, while the remaining 3.30% was influenced by other factors not included in the research model.Keywords: NPF, BOPO, FDR, ROA